IMPROVING MANAGEMENT OF TAX OFFENSE DETECTION IN THE DIGITAL ECONOMY - Ilhom Nosirov; Anvarjon Makhmudov (Scholar Express Journals, 2023)
This article describes the main results of scientific research in the field of development and improvement of the tax system in our country and scientific research aimed at preventing and eliminating tax offenses within the priority areas of economic reforms implemented in the country. The root causes of tax evasion and tax evasion are analyzed in detail. Based on the relevance of the problem, the need for the introduction of effective mechanisms aimed at removing the influence of obstacles on economic management, especially the tax system, and the creation of a systematic management of the use of such
Keywords: Tax management; tax offenses; tax evasion; tax base